Taiwanese College Students' Perceptions of Plagiarism: Cultural and Educational Considerations. Issue 2 (17th February 2017) - Chien, Shih-Chieh
Abstract : The present study investigates Taiwanese college students' perceptions of plagiarism. Specifically, this study seeks to explore how perceptive students pursuing higher education in Taiwan are in recognizing plagiaristic writing, in what terms they perceive source use in writing as appropriate and inappropriate, and view why plagiarism occurs. The study included 30 high- and 30 low-achieving students selected out of 396 students in English writing classes at a university in Taiwan. Drawing upon evidence from a writing exercise and individual interviews with these 60 Taiwanese college students, the present study identified a variety of reasons why students may plagiarize. Most of the students participating in the study had some basic understanding of plagiarism. They had some familiarity with the Western notion of plagiarism, but based on the writing exercise, more often than not they were not able to recognize plagiarism when it actually occurred. Students' understanding was generally, but not entirely, consistent with their source use behavior. More than half of the students considered that plagiarism is a cultural issue. However, there are also other factors that may lead to plagiarism. Finally, recommendations in terms of writing pedagogy are made.